Photodynamic Antimicrobial Chemotherapy for Root Canal System Asepsis: A Narrative Literature Review - P. Diogo; T. Gonçalves; P. Palma; J. M. Santos (International Journal of Dentistry)
Aim. The aim of this comprehensive literature review was to address the question: Does photodynamic therapy (PDT) improve root canal disinfection through significant bacterial reduction in the root canal system? Methodology. A comprehensive narrative literature review was performed to compare PDT effect with sodium hypochlorite as the comparative classical irrigant. Two reviewers independently conducted literature searches using a combination of medical subject heading terms and key words to identify relevant studies comparing information found in 7 electronic databases from January 2000 to May 2015. A manual search was performed on bibliography of articles collected on electronic databases. Authors were contacted to ask for references of more research not detected on the prior electronic and manual searches. Results. The literature search provided 62 titles and abstracts, from which 29 studies were related directly to the search theme. Considering all publications, 14 (48%) showed PDT to be more efficient in antimicrobial outcome than NaOCl (0.5–6% concentration) used alone and 2 (7%) revealed similar effects between them. Toluidine blue and methylene blue are the most used photosensitizers and most commonly laser has 660 nm of wavelength with a 400 nm diameter of intracanal fiber. Conclusions. PDT has been used without a well-defined protocol and still remains at an experimental stage waiting for further optimization. The level of evidence available in clinical studies to answer this question is low and at high risk of bias.